Down-regulation of HLA-G Attenuates Cleavage Rate in Human Triploid Embryos - LL Sun; A Ming Wang; Ch J Haines; Y Han; Y Qing Yao (JRI, 2011)
Background: HLA-G is a major histocompatibility complex (MHC), class Ib molecule that is selectively expressed at the fetal–maternal interface. It is thought to play a role in protecting the fetus from the maternal immune response. Interestingly, the preimplantation embryo development (Ped) gene product Qa-2 is also a mouse MHC class Ib protein that affects cleavage and division of preimplantation mouse embryos and subsequent embryonic survival. Data from many human in vitro fertilization (IVF) clinics suggest that the mouse Ped phenomenon also exists in human because embryos fertilized at the same time have different cleavage rates and consequently different IVF outcomes. As HLA-G is expressed in human early embryos, it is highly regarded as the functional homologue of Qa-2. Whether HLA-G expression is correlated with the cleavage rate of human embryos has great potential clinical value. Methods: In this study, 45 human early abnormal fertilized embryos (3 PN) from patients undergoing in vitro fertilization were used to test the effects of HLA-G knock-down via infection with adenovirus carrying its specific siRNA on the cleavage rate in a 2-day culture period. One- way ANOVA, Post hoc and Chi-square were used to compare groups. A p-value smaller than 0.05 was considered statistically significant. Results: Knocking-down HLA-G in human preimplantation stage embryos resulted in a higher cell arrest rate and a slower cleavage rate. Conclusion: The results from the present study suggested that HLA-G might play an important role in early human embryo development.
Keywords: Adenovirus, Cleavage, HLA-G, In Vitro fertilization, Mouse Qa-2 antigen, Preimplantation embryo, RNAi, Adenovirus vector